3x+11=7x+3

Simple and best practice solution for 3x+11=7x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+11=7x+3 equation:


Simplifying
3x + 11 = 7x + 3

Reorder the terms:
11 + 3x = 7x + 3

Reorder the terms:
11 + 3x = 3 + 7x

Solving
11 + 3x = 3 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
11 + 3x + -7x = 3 + 7x + -7x

Combine like terms: 3x + -7x = -4x
11 + -4x = 3 + 7x + -7x

Combine like terms: 7x + -7x = 0
11 + -4x = 3 + 0
11 + -4x = 3

Add '-11' to each side of the equation.
11 + -11 + -4x = 3 + -11

Combine like terms: 11 + -11 = 0
0 + -4x = 3 + -11
-4x = 3 + -11

Combine like terms: 3 + -11 = -8
-4x = -8

Divide each side by '-4'.
x = 2

Simplifying
x = 2

See similar equations:

| 6(y-3)=24 | | 240=4w+11g | | x+7-3x=16-5x+3 | | 1.2x=.72 | | 5x-20+3=7x | | 4=7w+6 | | 4x+6=2(x+8) | | 3x=7x-20 | | 7x-3=5-2x | | 3x-2x+1=x+6 | | 3x+11+7x+3=180 | | 12=3(x-9) | | 3x+5x+10=10x-2x+10 | | 12z^3=14z^2+48z | | 2x+18=4x+10 | | 7-4y=7 | | -9x-5y=27 | | 2*(ln(x))+1=0 | | x-4(x+3)=12 | | 8q+5=2 | | 50q-43=52q-18 | | 250=14w+9g | | 6x-1=7(x+9) | | 2(x-8)=2x+6 | | 2x^2+10X+3=3 | | 4.5g+0.75=18.75 | | 4.5+0.75=18.75 | | 3x=5(x+3)-s | | f(x)=3x^2-9x+6 | | -4=2-3p | | 4k-5=-17 | | -15r+5=50 |

Equations solver categories